TYPOLOGICAL CHARACTERISTICS OF THE LYRICS OF THE ANCIENT PERIOD (World Bulletin of Social Sciences, 2024)
In the article, the typological and specific aspects of the samples of the lyric type in ancient Eastern and Western literature are analyzed. The leading genres, forms and expressive features of ancient Eastern and Western lyrics are studied in the context of comparative literary studies. In ancient Eastern and Western literature, the rhyming and weight characteristics of lyrical genres, as well as its subject content, were thoroughly studied. Also, the influence of theological, mythological and folklore sources on the lyrics of the ancient world, the development principles of Arabic poetry in the East, and the manifestations of Ancient Greek lyrics in the West are discussed.